Research on the Privacy Protection Mechanism of Multimodal Fusion of Data Based on Blockchain Technology - Na, Renhua; Jiao, Yang; Yang, Liu (International Conference on Information Systems and Computer Aided Education (Online), 2024)
Firstly, this mechanism uses multi-modal fusion algorithm to integrate Basic data from different sources and different types effectively, which improves the accuracy and efficiency of data analysis. At the same time, in order to ensure the privacy and security of data transmission and storage process, the certificateless public key system (CL-PKI) is introduced, which reduces the risk of information leakage in the intermediate link through the characteristics of no third-party certification authority. In addition, the privacy protection ability of the system is further enhanced by anonymizing the identities of both parties. In the stage of system simulation, a series of experiments are designed to verify the effectiveness of the proposed mechanism. The results show that this mechanism not only ensures data integrity and consistency, but also significantly improves the privacy protection level of Basic data processing. Compared with traditional Basic data management systems, this mechanism has significant advantages in terms of security, reliability and user experience. The multimodal fusion privacy protection mechanism of Basic data based on blockchain technology proposed in this paper provides a new solution for data security management in the data security, and has important theoretical value and practical application prospects.